2016
DOI: 10.1002/stem.2511
|View full text |Cite
|
Sign up to set email alerts
|

Neurotrophic Factor-α1: A Key Wnt-β-Catenin Dependent Anti-Proliferation Factor and ERK-Sox9 Activated Inducer of Embryonic Neural Stem Cell Differentiation to Astrocytes in Neurodevelopment

Abstract: Embryonic neurodevelopment involves inhibition of proliferation of multipotent neural stem cells followed by differentiation into neurons, astrocytes and oligodendrocytes to form the brain. We have identified a new neurotrophic factor, NF-α1, which inhibits proliferation and promotes differentiation of neural stem cell/progenitors derived from E13.5 mouse cortex. Inhibition of proliferation of these cells was mediated through negatively regulating the Wnt pathway and decreasing β-catenin. NF-α1 induced differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 88 publications
(124 reference statements)
0
30
0
Order By: Relevance
“…Moreover, the results also showed that the DEGs we re associated with regulation of the ERK1 and ERK2 cascade. A previous study revealed that a novel neurotrophic factor, NF-α1, can induce the differentiation of NSCs to astrocytes by activating the ERK1/2-Sox9 signaling path way [31]. Folate is also involved in regulating the proliferation and reduced apoptosis of NSCs accompanied by ERK1/2 phosphorylation [32].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the results also showed that the DEGs we re associated with regulation of the ERK1 and ERK2 cascade. A previous study revealed that a novel neurotrophic factor, NF-α1, can induce the differentiation of NSCs to astrocytes by activating the ERK1/2-Sox9 signaling path way [31]. Folate is also involved in regulating the proliferation and reduced apoptosis of NSCs accompanied by ERK1/2 phosphorylation [32].…”
Section: Discussionmentioning
confidence: 99%
“…Membranes were probed overnight at 50°C with the DIG-labeled mCPE probe directed to the mCPE open reading frame (ORF). After 6 washes (described in the Ambion protocol), the membranes were processed for immunodetection by using an anti-DIG-AP antibody (1:10,000; F. Hoffmann-La Roche) and visualized with disodium 3-(4-methoxyspiro {1,2-dioxetane-3,29-(59-chloro)tricyclo [3.3.1.1 3,7 ]decan}-4yl)phenyl phosphate (CSPD; 1:100, 11655884001; Roche) against X-film.…”
Section: Northern Blot Analysismentioning
confidence: 99%
“…The enzymatic activity of CPE-DN was analyzed by HPLC. A) Sequence of ACTH (1-17)-(1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) showing cleavage sites for CPE at C-terminal basic amino acid residues. B) Lysates from CPE-WT, CPE-DN, or control adenovirus-infected COS-7 cells were incubated for 24 h with ACTH (1-17), with and without cobalt and/or GEMSA, and the enzymatically processed products were analyzed by HPLC.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The Wnt signaling pathway has been implicated in the modulation of self‐renew and cell fate in diverse stem cells (Aubert et al, ; Anakwe et al, ; Bi et al, ; Cain and Manilay, ; Huang et al, ; Lee et al, ; Selvaraj et al, ; Leiros et al, ). The secreted Frizzled‐related proteins (SFRPs) are considered to be the endogenous antagonists of the Frizzled receptors of Wnt proteins, which contain a homologous region to Frizzled but lack a transmembrane domain to transmit signals (Lee et al, ).…”
Section: Introductionmentioning
confidence: 99%